Association of Cannabis Use With Nausea and Vomiting of Pregnancy. Issue 2 (6th August 2022) - Metz, Torri D.; Allshouse, Amanda A.; McMillin, Gwendolyn A.; Silver, Robert M.; Smid, Marcela C.; Haas, David M.; Simhan, Hyagriv N.; Saade, George R.; Grobman, William A.; Parry, Samuel; Chung, Judith H.; Jarlenski, Marian P.
Abstract : Cannabis use as ascertained by urine assay for marijuana metabolite was associated with a higher likelihood of moderate-to-severe nausea and vomiting in early pregnancy. Abstract : Our objective was to evaluate whether cannabis use was associated with nausea and vomiting in early pregnancy. Participants from nuMoM2b (Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-to-Be) enrolled from October 2010 through September 2013 with a PUQE (Pregnancy-Unique Quantification of Emesis) questionnaire and an available stored urine sample from the first study visit (median gestational age 12 weeks) were included. Cannabis exposure was ascertained by urine immunoassay for 11-nor-9-carboxy-delta-9-tetrahydrocannabinol (THC-COOH); positive results were confirmed with liquid chromatography tandem mass spectrometry. The primary outcome was moderate-to-severe nausea by the PUQE score. Overall, 9, 250 participants were included, and 5.8% (95% CI 5.4–6.3%) had detectable urine THC-COOH. In adjusted analyses, higher THC-COOH levels were associated with greater odds of moderate-to-severe nausea (20.7% in the group with THC-COOH detected vs 15.5% in the group with THC-COOH not detected, adjusted odds ratio 1.6, 95% CI 1.1–2.2 for a 500 ng/mg Cr THC-COOH increment).